FAILURE ANALYSIS AND EXPERIMENTAL STUDY OF COMPOSITE MULTI-PIN CONNECTIONS BASED ON CONTINUUM DAMAGE MECHANICS - LI Xi; LI YaZhi; MO ChengJie; QIN Qun; CHEN Hong (Jixie qiangdu)
Composite multi-pin connection is a common connection form in engineering structure. In this paper, numerical analysis and experimental study on the failure and damage of composite multi-pin connection structure under tensile load are carried out. Firstly, different failure criteria are established for fiber, matrix and delamination. Based on fracture mechanics, the strength parameters of single-layer plate considering in-situ effect are derived. Combined with the method of stiffness exponential decay, the continuous damage mechanical constitutive model of composite single-layer plate is compiled by using finite element subroutine. In order to improve the calculation efficiency, this paper proposes to use the partition Newton method, which is different from the traditional Puck method and the partition golden section method, to calculate the angle of matrix failure fracture surface in Puck failure criterion. Secondly, the tensile properties of composite laminate plate and perforated plate are analyzed by using the above mechanical model, and the feasibility of the model is verified by comparing the test results. Finally, the failure and damage evolution process of the composite multi pin connection structure is analyzed by using the above mechanical model, and the results are compared with the experimental results. The results show that the mechanical model proposed in this paper can predict and calculate the mechanical response and damage mode of carbon fiber composite multi-pin connection structure under tensile load.